(untitled) (International Journal of Occupational Safety and Health, 2022)
Introduction: Work-related musculoskeletal disorders (WMSD) are conditions in which the work environment and performance of work contribute significantly to the musculoskeletal condition. The objective of this study was to assess the work-related musculoskeletal disorders among the pesticide sprayers in tea plantations. Methods: A cross-sectional study was conducted among 290 chemical sprayers in selected tea plantations in South India from September to October 2018. Simple random sampling was done to select the sprayers for the study, written informed consent was taken and face–to–face interview was done with the sprayers. Socio-demographic factors and work profiles were noted. The Nordic Musculoskeletal Questionnaire was used for the evaluation of musculoskeletal complaints. Results: Among the 290 sprayers in the study, all of them were males and the mean age of the participants was 45.6±8.5 years. More than half of the study participants 152 (52.4%) suffered from at least one musculoskeletal complaint and most of them 104 (35.8%) had pain in more than one body part. Among them, more than one-third 101 (34.8%) suffered from knee joint pain in the past twelve months. Shoulder problems (27.6%), lower back (22.8%) and upper back pains (19.3%) were the other major work-related musculoskeletal disorders that the study participants faced in the past year. Knee pain (31.7%), low backache (20.7%) and shoulder pain (24.1%) were the musculoskeletal problems that were related to their absence from work. Conclusion: More than half of the sprayers had at least one musculoskeletal complaint. Most common issues included knee joint pain, shoulder pain and back pains.